A prática pedagógica dos professores do ensino da educação de jovens e adultos: dificuldades e desafios - GOMES, Marivalda Correa (2024)
This study discusses the pedagogical practice focused on the Education of Young and Adults - EJA. Beginning with a brief historical review, following with the obligatoriness and with the necessity of a pedagogical practice focused on the singularity and totality of the subject. Addressing the realities and perspectives along the need of educational methods, analyzing the difficulties and challenges that are found in the EJA, so that the difficulties are discussed and solutions are presented, valuing the best performance of the students' learning and achievement.